Comparison of Writing Drama Text Skills Between Eleventh-Grade Science 1 Students and Eleventh-Grade Social Students at SMA Negeri 1 Bandar Sei Kijang - Mhd. Virzha Nafandri Utama; Isah Cahyani; Khaerudin Kurniawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the use of technological media and the students’ writing drama text skills between Class XI IPA 1 and XI IPS at SMA N 1 Bandar Sei Kijang. The research method used is the descriptive qualitative method. The research instrument is an interview questionnaire guideline that will be administered to Indonesian teachers. The research was conducted at SMA N 1 Bandar Sei Kijang with 23 students of class XI IPA 1 and 21 students of class XI IPS 1. The data collection technique in the study was to use interview guidelines, which contain questions about students’ learning conditions, students’ learning achievements, and students’ learning outcomes by applying different media and methods. The results indicate that technology media with the question and answer method was more effective to use than print media with the lecture method. It was proven based on the interviews. The students who used technology media with the question and answer method obtained results that tended to be high with a value of 83.52. The use of technology in learning can ease students and teachers to carry out learning.